A St Petersburg Paradox for risky welfare aggregation. (27th May 2021) - Goodsell, Zachary
Abstract: The principle of Anteriority says that prospects that are identical from the perspective of every possible person's welfare are equally good overall. The principle enjoys prima facie plausibility, and has been employed for various theoretical purposes. Here it is shown using an analogue of the St Petersburg Paradox that Anteriority is inconsistent with central principles of axiology.